2014
DOI: 10.3390/toxins6051471
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal enterotoxins in the Etiopathogenesis of Mucosal Autoimmunity within the Gastrointestinal Tract

Abstract: The staphylococcal enterotoxins (SEs) are the products of Staphylococcus aureus and are recognized as the causative agents of classical food poisoning in humans following the consumption of contaminated food. While illness evoked by ingestion of the SE or its producer organism in tainted food are often self-limited, our current understanding regarding the evolution of S. aureus provokes the utmost concern. The organism and its associated toxins, has been implicated in a wide variety of disease states including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…Thus, SEs are shown to be involved in pneumonia, toxic shock syndrome, sepsis‐related infections and food poisoning (Balaban & Rasooly, ; Langley, Patel, Jackson, Clow, & Fraser, ; Lappin & Ferguson, ; Lowy, ; Ortega, Abriouel, Lucas, & Gálvez, ). In addition, recent studies suggest a broader role of SEs in other illnesses, including the respiratory tract (Huvenne, Hellings, & Bachert, ; Pastacaldi, Lewis, & Howarth, ) and autoimmune diseases (Li et al, ; Principato & Qian, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SEs are shown to be involved in pneumonia, toxic shock syndrome, sepsis‐related infections and food poisoning (Balaban & Rasooly, ; Langley, Patel, Jackson, Clow, & Fraser, ; Lappin & Ferguson, ; Lowy, ; Ortega, Abriouel, Lucas, & Gálvez, ). In addition, recent studies suggest a broader role of SEs in other illnesses, including the respiratory tract (Huvenne, Hellings, & Bachert, ; Pastacaldi, Lewis, & Howarth, ) and autoimmune diseases (Li et al, ; Principato & Qian, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 20 SEs or enterotoxin-like proteins (SE l s) have been identified and designated as SEA to typically SE l V [ 1 , 7 ]. Okumura et al [ 8 ] reported also SE l W. Some of them are emetic agents (SEA to SEI, SER, SES, SET) and are a major cause of food poisoning [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcal enterotoxins (SEs) (superantigens) have been considered as one of the most common causative agents of bacterial food-borne disease outbreaks worldwide ( 1 ), and intensive research has been performed on both people’s ( 2 ) and animal’s staphylococcal toxigenic isolates ( 3 ). Consequently, it is well established that SEs are the major cause of food poisoning ( 4 ). In addition all SEs possess superantigenic activity and induce the inflammatory cytokines storm and inflammatory disease ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%